From the Mediterranean to the Americas. Italian Ethnic Schools in Rio Grande do Sul between Emigration, Colonialism and Nationalism (1875-1925) - Barausse, Alberto (2016)
Between the second half of the nineteenth century and the first decades of the twentieth century, the development of Italian educational institutions has been associated with new processes. The needs related to the formation of Nation-State, widen and intertwined with those determined by new phenomena as the colonialism and massive emigration. Millions of Italians crossed the Mediterranean to reach the coasts of the Americas: there arose new colonies of immigrants. The dynamics that involved the Italian society have requested schools to take on new and relevant functions for the basic education of citizens in the states of emigration and in those of colonization. The essay presents the case study of Italian ethnic schools abroad: it aims to examine the functions performed by institutions and school cultures—by textbooks—used to ensure the preservation and the promotion of specific educational models by ethnical and identitary characteristics in a national sense in a different context, like the Brazilian State of Rio Grande do Sul.